EFFECT OF ADDING KAOLIN WITH NATURAL AND RECYCLED COARSE AGGREGATES ON ASPHALT MIXTURE - W. Majeed, Muhannd (Journal of Engineering and Sustainable Development, 2017)
Last few years interesting in, recycled coarse aggregate (derived from old concrete) was increased in pavement construction. This type of aggregate has good results approximately and economically from natural coarse aggregate results. In this research Kaolin was used as a filler material addition in percentages (0, 5, 10, 15, and 20%) by weight of cement to know the effect of that type of filler material on asphalt mixture. The values show that the flow of asphalt mixture is between (2-5) mm, this is more accepted with recycled aggregate than the natural aggregate especially of mix (0 and 5%) of adding Kaolin. Also, the use of recycled aggregates gives values of stability of asphalt mixture more than the natural aggregates.